Effects of blood flow restriction training on bone metabolism: a systematic review and meta-analysis - Wang, Xiaolin; Wang, Yifei; Yang, Xuezhen; Mohd Nasiruddin, Nasnoor Juzaily Bin; Dong, Delong; Samsudin, Shamsulariffin Bin; Qin, Xin-Min (Frontiers in Physiology, 2023)
The efficacy of low-intensity blood flow restriction (LI-BFR) training programs in bone metabolism remains unclear compared to low-intensity (LI) training and high-intensity (HI) training. The aim of this review was to quantitatively identify the effects of LI-BFR training on changes in bone formation markers (i.e., bone-specific alkaline phosphatase, BALP), bone resorption (i.e., C-terminal telopeptide of type I collagen, CTX) and bone mineral density (BMD) compared with conventional resistance training programmes. Additionally, the effectiveness of walking with and without BFR was assessed. PubMed, Scopus, SPORTDiscus, Web of Science and Google Scholar databases were searched for articles based on eligibility criteria. Review Manager Version 5.4 was used for Metaanalysis. Physiotherapy Evidence Database (PEDro) was applied to assess the methodological quality of studies. 12 articles were included in the meta-analysis, with a total of 378 participants. Metaresults showed that compared with LI training, LI-BFR training induced greater increments in BALP